Photoinactivation of Planktonic Cells, Pseudohyphae, and Biofilms of Candida albicans Sensitized by a Free-Base Chlorin and Its Metal Complexes with Zn(II) and Pd(II) - Cordero Gabrielli, Paula Verónica (2023)
Invasive candidiasis is an important cause of morbidity and mortality, and its occurrence is increasing due to the growing complexity of patients. In particular, Candida albicans exhibits several virulence factors that facilitate yeast colonization in humans. In this sense, the photodynamic inactivation of yeasts is a promising new alternative to eliminate fungal infections. Herein, the photodynamic activity sensitized by a free-base chlorin (TPCF16) and its complexes with Zn(II) (ZnTPCF16) and Pd(II) (PdTPCF16) was investigated in order to eliminate C. albicans under different forms of cell cultures. A decrease in cell survival of more than 5 log was found in planktonic cells incubated with 5 μM TPCF16 or ZnTPCF16 upon 15 min of white-light irradiation. The mechanism of action mainly involved a type II pathway in the inactivation of C. albicans cells. In addition, the photodynamic action induced by these chlorins was able to suppress the growth of C. albicans in a culture medium. These photosensitizers were also effective to photoinactivate C. albicans pseudohyphae suspended in PBS. Furthermore, the biofilms of C. albicans that incorporated the chlorins during the proliferation stage were completely eradicated using 5 μM TPCF16 or ZnTPCF16 after 60 min of light irradiation. The studies indicated that these chlorins are effective photosensitizing agents to eliminate C. albicans as planktonic cells, pseudohyphae, and biofilms.